Flat‐top pumped multi‐millijoule mid‐infrared parametric chirped‐pulse amplifier at 10 kHz repetition rate - Zou, Xiao (2021)
The advancement of mid-infrared (MIR) parametric amplification technique serves as the main driving force of multiple strong-field experiments in the frontier of science such as the generation of coherent soft X-ray and isolated attosecond pulses. However, the low parametric down-conversion efficiency especially in the MIR wavelength is a major bottleneck that hinders the further exploration of the MIR-laser-driven strong-field physics. Here, a simple and robust method that doubles the efficiency of a MIR optical parametric chirped-pulse amplifier (OPCPA) is reported, as a demonstration of the concept, through engineering a flat-top pump profile via high-efficiency diffractive optical elements. With the proposed flat-top pump scheme, a MIR OPCPA system at 3 m and 10 kHz repetition rate with both the record pulse energy of 2.7 mJ and the highest average power at 27 W among the MIR OPCPAs with kHz repetition rate is demonstrated. This work provides a promising approach for achieving high energy high power MIR few-cycle lasers that can be readily used in emerging strong field experiments. In addition, it is believed that the developed technique in this work can become a general method of parametric efficiency enhancement, which is applicable to other nonlinear conversions and wavelength ranges.